Chapter Il caso studio del Molise - Monturano, Gianluca (Studi e saggi, 2020)
Basing on multivariate statistical methods, text and sentiment analysis, and profitability analysis, a study is performed, with the aim to define the role of Community-based cooperatives in the development process of the inner areas of the Italian region of Molise. Census data, direct interviews data, and balance sheets data are employed to identify a new model of local development based on cooperative principles.